2010
DOI: 10.1016/j.ibiod.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

PLFAs of the microbial communities in composting mixtures of agro-industry sludge with different proportions of household waste

Abstract: Phospholipid fatty acids (PLFAs) were analysed at different time periods during composting of two waste mixtures rich in fats, M1 (22%) and M2 (39%), with the aim of monitoring changes in microbial community structure. The two mixtures consisted of a sludge sample collected from a vegetable oil refinery effluent treatment plant combined with household wastes. The PLFA profiles of both mixtures revealed that, at the start of the process, fungi and Gram-negative bacteria (GÀ) were more abundant in M2 than in M1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…Nonetheless, a decrease in temperature did not produce an observable increase in how abundant fungi were; both treatments, however, were characterized by the fungal biomass being predominant, particularly in the case of static treatment, throughout the entire process. Amir et al [44] found that fungi are more present in wastes with a high level of fatty acids. Likewise, Villar et al [13] suggested that the influence the initial material, in this case lipid in nature and pH, has on the maturation phase is reflected by microbial diversity; this means that although the waste undergoes significant degradation during the composting process, the properties of the starting material determine the dominant microbial groups throughout the maturation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a decrease in temperature did not produce an observable increase in how abundant fungi were; both treatments, however, were characterized by the fungal biomass being predominant, particularly in the case of static treatment, throughout the entire process. Amir et al [44] found that fungi are more present in wastes with a high level of fatty acids. Likewise, Villar et al [13] suggested that the influence the initial material, in this case lipid in nature and pH, has on the maturation phase is reflected by microbial diversity; this means that although the waste undergoes significant degradation during the composting process, the properties of the starting material determine the dominant microbial groups throughout the maturation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Le compostage est un processus aérobie de dégradation des composés organiques par l'action successive des micro-organismes (bactéries et champignons) dont la concentration peut atteindre des millions par gramme de compost (Barje et al, 2008, Jouraiphy, 2007, Amir, 2005Amir et al, 2010) ; leur évolution est en fonction des stades de compostage avec un profil défini, en fonction des espèces, à la nature et la structure des substrats et aussi liée principalement aux variations des paramètres physico-chimiques (Rosenzweig et al, 1980). Au cours du processus de compostage réalisé, la flore microbienne varie considérablement ( fig.9).…”
Section: Evolution De La Flore Microbienneunclassified
“…The iso and anteiso-(i, a) in C15:0; C16:0 and C17:0 are commonly used as signature fatty acids for bacteria, especially Gram-positive bacteria, [4,13] as well as C15:0, C17:0 which indicate non-specific bacteria; and unsaturated fatty acids C18:1ω7c, C18:1ω9c indicate a bacterial origin especially Gram-negative. [15,16] The levels of total lipid and of total FAMEs during the two co-composting trials are plotted in Figure 1(a) and 1(b).…”
Section: Fame Patternsmentioning
confidence: 99%
“…[10] This fall in the level of extractable lipid supports the work of numerous authors studying waste composting. [13,17] It can be attributed to their breakdown by the intense microbial activity, nevertheless, it has been shown [18] that lipids which are not directly extractable are less biodegradable, for instance those chemically bonded to organic matter or adsorbed by the mineral matrix. After the decrease in extractible lipids, significant increases in FAMEs occurred during co-composting in both trials: FAMEs rose by 8.44-33.30% and 10.76-43.40% for mixtures A and B, respectively.…”
Section: Fame Patternsmentioning
confidence: 99%
See 1 more Smart Citation